Unilateral Hypertrophy of the Mandibular Condyle - Raibagkar, Santosh; Patel, Jayesh; Vyas, U. H. (Indian Journal of Plastic Surgery, 1986)
Unilateral hypertrophy of the mandibular condyle is not an uncommon entity. About 150 case have been reported so far. From India, Only two cases have been reported. On account of this rarity, it is our pleasure to report the following case.